Proceedings of the Twenty-Ninth International Joint Conference on Artificial Intelligence 2020
DOI: 10.24963/ijcai.2020/753
|View full text |Cite
|
Sign up to set email alerts
|

DeepVentilation: Learning to Predict Physical Effort from Breathing

Abstract: Tracking physical effort from physiological signals has enabled people to manage required activity levels in our increasingly sedentary and automated world. Breathing is a physiological process that is a reactive representation of our physical effort. In this demo, we present DeepVentilation, a deep learning system to predict minute ventilation in litres of air a person moves in one minute uniquely from real-time measurement of rib-cage breathing forces. DeepVentilation has been trained on input signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In C2, SZ required data from the Norwegian Institute of Sports Science to create physical and deep learning models to predict respiratory minute ventilation from ribcage movement data. Since the data collection process is cumbersome, the development of the deep learning models was based on maximizing the use of deep learning techniques that can generalize reasonably well from small data and discuss the risks of faulty prediction for unforeseen data [55]. In C3, sensor data from machine tools such as CNC milling, turning, broaching, and grinding is needed to develop tools to validate and improve data quality for Industry 4.0.…”
Section: P13: Anticipate Unavailability Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In C2, SZ required data from the Norwegian Institute of Sports Science to create physical and deep learning models to predict respiratory minute ventilation from ribcage movement data. Since the data collection process is cumbersome, the development of the deep learning models was based on maximizing the use of deep learning techniques that can generalize reasonably well from small data and discuss the risks of faulty prediction for unforeseen data [55]. In C3, sensor data from machine tools such as CNC milling, turning, broaching, and grinding is needed to develop tools to validate and improve data quality for Industry 4.0.…”
Section: P13: Anticipate Unavailability Of Datamentioning
confidence: 99%
“…In C2, SZ had the long term goal of developing a mathematical model to predict respiratory flow from ribcage movement data obtained from their Flow sensor. This work required collaboration with the Norwegian School of Sports Science to obtain data to verify the validity of a physical model and also test new techniques in deep learning [55]. Data acquisition from an exercise spirometer and the Flow sensor developed by SZ was a long-term task that was performed in parallel and remotely by the sports school.…”
Section: P14: Define Long-term Tasks That Enable Remote Collaborationmentioning
confidence: 99%
“…Again, changes may be required if any operations are not supported because of differences in library support across models. For example, in [108], the conversion process was accomplished via the conversion of PyTorch to the Onnx standard and then to TensorFlow and TensorFlow.js.…”
Section: Converting Python Models Into Tensorflowjs Modelsmentioning
confidence: 99%
“…Signal analysis A virtual laboratory for EEG data analysis that enables data analysis, pre-processing, and model development was built with TensorFlow.js in [3]. Using realtime sensor measurements of rib-cage movement, a separate clinical study in [108] found that an LSTM network model can predict physical effort by comparing how much air a person breathes in a minute to their perceived workout intensity.…”
Section: Video Image and Signal Analysis Appsmentioning
confidence: 99%
“…We have previously investigated how minute ventilation in litres per minute can be estimated from ribcage RIP signals using a machine learning approach called DeepVentilation. 17 Deep learning presents the possibility to take into account individual differences such as age, gender weight, height, variation in the placement of sensors across several different people. It offers the possibility to improve prediction and specificity over time with more availability of data.…”
Section: Related Workmentioning
confidence: 99%